Driving Characteristics Analysis of Light-duty Vehicle RDE Test in Plain and Plateau. Issue 1 (November 2020) - Lyu, H; Li, J; Fu, T
Abstract: In this paper, 8 real-driving emission (RDE) tests were conducted by using a portable emission measurement system (PEMs), and the intensity value was defined to quantitatively express the driving intensity of vehicles. Four plains RDE experiment and four plateau RDE driving characteristics were analysed. At the same time, the transient characteristics of plain test 3 and plateau test 2 with close and stable driving intensity and plain test 1 with high driving intensity were compared. Results show that compared with the plain RDE test, driving intensity of plateau RDE test overall is low, and the frequent acceleration and deceleration times of the plateau RDE test in the urban section are few, besides the acceleration is relatively large. The intensity of driving can have a big impact on pollutant emissions, especially in highway section. The acceleration of the plateau RDE test in the urban section is large, and the CO emission is high due to the climatic conditions and road conditions. Therefore, the frequent acceleration process of the plateau test in the urban section should be paid special attention to when the vehicle is conducting calibration test. In conclusion, from a test method point of view, the driving intensity of the RDE test should be required; From the point of view of calibration development, we should focus on the condition of high driving intensity.